2013
DOI: 10.7573/dic.212260
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment for attention deficit hyperactivity disorder: functional outcomes in children and adolescents from non-Western countries

Abstract: Objective:Functional outcomes were measured over a 12-month period in children and adolescents with attention deficit hyperactivity disorder (ADHD) after they received monotherapy.Design:Prospective, observational, noninterventional study.Setting:Conducted in six non-Western countries.Participants:Outpatients 6 to 17 years of age with a verified diagnosis of ADHD in accordance with the Diagnostic and Statistical Manual, Fourth Edition, Text Revision (DSM-IV-TR), together with their physicians, decided to initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…The current study was a post‐hoc analysis of data from a noncomparative, prospective, observational, 12‐month trial in 546 outpatients aged 6–17 years from China ( n = 126), Egypt ( n = 90), Lebanon ( n = 59), the Russian Federation ( n = 142), Taiwan ( n = 79), and the United Arab Emirates ( n = 50) (Altin et al ., ) who were diagnosed with ADHD. Patients' diagnoses of ADHD were verified in clinical psychiatric interviews in accordance with the Diagnostic and Statistical Manual, Fourth Edition, Text Revision (DSM‐IV‐TR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study was a post‐hoc analysis of data from a noncomparative, prospective, observational, 12‐month trial in 546 outpatients aged 6–17 years from China ( n = 126), Egypt ( n = 90), Lebanon ( n = 59), the Russian Federation ( n = 142), Taiwan ( n = 79), and the United Arab Emirates ( n = 50) (Altin et al ., ) who were diagnosed with ADHD. Patients' diagnoses of ADHD were verified in clinical psychiatric interviews in accordance with the Diagnostic and Statistical Manual, Fourth Edition, Text Revision (DSM‐IV‐TR).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study demonstrated that clinical and functional outcomes were improved in children and adolescents with ADHD from non‐Western countries who initiated and continued taking their prescribed pharmacological treatment (Altin et al ., ). A variety of predictors of medication adherence and persistence in ADHD have been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…In our main trial, Altin et al. found that, after 12 months of treatment, clinical and functional outcomes were improved in children and adolescents from non‐Western countries who initiated and remained on their prescribed pharmacological monotherapy . The main objective of this post hoc analysis of the aforementioned study was to examine clinical and demographical predictors of remission of ADHD in a non‐Western cohort of paediatric and adolescent patients with ADHD treated with atomoxetine or methylphenidate over the course of 12 months.…”
Section: Introductionmentioning
confidence: 95%
“…Представляют интерес недавно опубликованные результаты международного исследования «Двенадца-тимесячное проспективное наблюдательное исследова-ние функциональных изменений состояния у детей и под-ростков, которым было назначено медикаментозное лечение по поводу синдрома дефицита внимания с гипер-активностью (СДВГ)» [16]. Его целью было определение функциональных изменений у детей и подростков с СДВГ из разных стран, которым в обычных условиях была назначена монотерапия по поводу СДВГ на протяжении 1 года, с помощью оценки по разделу «Собственные достижения» шкалы CHIP-CE [17].…”
unclassified
“…Значительный регресс симптомов СДВГ был достигнут к концу исследования во всех трех терапевтических груп-пах. Одновременно во всех группах улучшилась средняя оценка по разделу «Собственные достижения» шкалы CHIP-CE (диапазон изменений в группах 2,0-19,0), что также отражает существенные положительные результа-ты проведенной терапии [16].…”
unclassified